Critical Incidents from Students-Teachers’ Action Research Teaching Journals in Pre-Service Teacher Education Program - Ardiyani Widya Permatasari (Journal of Foreign Language Teaching and Learning, 2018)
This paper presents a study about critical incidents in Action Research Teaching Journal (ARTJS) in Microteaching which comprised in five sections: topic, planning, action, observation and reflection. ARTJS was made before and after doing each mini teaching. Twelve ARTJSs were collected from four student-teachers who had taken Microteaching course. A descriptive data analysis was used to identify types of critical incidents found in ARTJSs by using NVIVO software tool. A critical incident has been defined as, “unanticipated events that occur during a lesson and trigger insights about some aspect of teaching and learning” (Farrel, 2005, pp.114-115), that lead them to be reflective teachers in ELT. The analysis began with coding the sections of the teaching journals which reflected types of critical incidents, then classified similar types of critical incidents into categories. The last step in the analysis was to interpret the categorized data. The analysis of the data shows that there were seven prominent themes that emerged from this study: course delivery problems, students’ participation, time management, technical problems, language proficiency problems and course preparation. The paper ends with some recommendation for improvement of Microteaching course.Keywords: action research, Microteaching, critical incidents.